Impact of Digital Literacy on Academic Achievement Of Undergraduate Students In Kanchanpur District, Nepal - Chand, Gambhir; Dhami, Nischal (Brixton Scholarly Review, 2026)
In the context of higher learning institutions, the concept of digital literacy has gained significant attention as a vital learning outcome in the modern era of technology-mediated learning environments, wherein students utilize technology extensively to achieve their academic objectives. While the prior literature established a strong relationship between academic achievement and digital literacy, there exists a lack of empirical evidence of the effect of digital literacy on the academic achievements of students in the context of the developing nations of the world, especially in the context of the nation of Nepal. In this context, the present study aims to investigate the effect of digital literacy on the academic achievements of undergraduate students in Kanchanpur District of Nepal. The descriptive-analytical method of research was used in the study, wherein the data were collected from a sample of 100 undergraduate students of Brixton College. The study found that the students have a moderate to high level of digital literacy skills, with a mean value of 3.95 on a five-point Likert scale. Moreover, the study established that the students have a higher level of skill in the practical application of technology than in the critical evaluation of online information. Finally, the study established a strong positive relationship between digital literacy skills and academic achievements of the students (r = .62, p < 0.01). Despite the positive outcomes of the study, there have been several challenges in the application of the skills of digital literacy.